Eksplorasi Senyawa Daun Kitolod (Isotoma longiflora) sebagai Agen Potensial untuk Kanker Prostat: Studi Farmakoinformatika - Muthia Nurhidayah (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2025)
Prostate cancer is one of the most prevalent malignancies in men and is strongly driven by dysregulation of androgen signaling, cell proliferation, and inflammation. Isotoma longiflora contains various bioactive compounds, yet their molecular relevance to prostate cancer remains unclear. This study aimed to identify the overlapping protein targets of Isotoma longiflora and prostate cancer and to elucidate the underlying molecular pathways. The methods included retrieval of protein targets from GeneCards, Venn analysis, construction of protein–protein interaction networks, clustering analysis, Gene Ontology and KEGG pathway enrichment, and molecular docking of key proteins. The analysis revealed 21 overlapping proteins, with ESR1, CDK2, and CASP9 identified as major hub proteins. Enrichment results indicated significant involvement of androgen receptor, MAPK, PI3K–Akt, p53 signaling, and steroid metabolism pathways. Molecular docking demonstrated that compounds such as Peonidin 3-(6’’-acetyl)glucoside, lobellin, and (-)-Gallocatechin-3-O-gallate showed strong binding affinity toward TNF, SIRT1, and PTGS2. These findings imply that Isotoma longiflora possesses potential as a source of prostate cancer therapeutic candidates by modulating multiple molecular pathways related to proliferation, apoptosis, and inflammation.